Increased expression of miR-93 is associated with poor prognosis in head and neck squamous cell carcinoma - Li, Guo (Tumour Biol, 2015)
MicroRNA-93-5p (miR-93) is a novel oncogenic microRNA (miRNA) and is elevated in diverse human malignancies. Aberrant expression and dysfunction of miR-93 are involved in many types of human tumours. However, the exact role of miR-93 remains unclear in head and neck squamous cell carcinoma (HNSCC). The objective of this study is to determine the expression pattern and clinical significance of miR-93 in HNSCC. MiR-93 expression levels in 103 primary HNSCC tissues and 16 corresponding non-cancerous epithelia were analysed by miRNA in situ hybridisation and correlated with the clinicopathological parameters and patient outcomes. Moreover, the expression of miR-93 was examined in four HNSCC cell lines and 17 pairs of HNSCC tissues and their corresponding adjacent tissues using quantitative real-time PCR (qRT-PCR). The miR-93 levels in HNSCC tissues and cell lines were significantly higher than those in the non-cancerous tissues. Notably, high miR-93 expression was significantly associated with T classification, lymph node metastasis and clinical stage. Kaplan–Meier survival analysis demonstrated that patients with high miR-93 expression had poorer overall survival than patients with low miR-93 expression. Multivariate Cox regression analysis revealed that miR-93 overexpression and lymph node metastasis were independent prognostic factors in patients with HNSCC. This study demonstrated that miR-93 expression was significantly increased in HNSCC tissue samples and cell lines and that miR-93 overexpression was associated with tumour progression, metastasis and poor prognosis in HNSCC patients. These results suggest that miR-93 may play a critical role in the initiation and progression of HNSCC, indicating that miR-93 may be a valuable marker for the prediction of metastasis and prognosis in HNSCC.